2019
DOI: 10.1038/s41401-019-0295-8
|View full text |Cite
|
Sign up to set email alerts
|

A new recombinant MS-superoxide dismutase alleviates 5-fluorouracil-induced intestinal mucositis in mice

Abstract: Intestinal mucositis is a common side effect of anticancer regimens that exerts a negative impact on chemotherapy. Superoxide dismutase (SOD) is a potential therapy for mucositis but efficient product is not available because the enzyme is degraded following oral administration or induces an immune reaction after intravascular infusion. Multi-modified Stable Anti-Oxidant Enzymes ® (MS-AOE ® ) is a new recombinant SOD with better resistance to pepsin and trypsin. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…The administration of SOD was therefore also tested in a model of 5-fluorouracil-induced intestinal mucositis in mice. The study showed that Multi-modified Stable Anti-Oxidant Enzymes ® (MS-AOE ® ), an rMnSOD obtained from a mutant high-temperature-resistant SOD strain, alleviates the mucositis caused by 5-fluorouracil, primarily in the first 3–5 days [ 172 ].…”
Section: Sod As a Detoxification Strategymentioning
confidence: 99%
“…The administration of SOD was therefore also tested in a model of 5-fluorouracil-induced intestinal mucositis in mice. The study showed that Multi-modified Stable Anti-Oxidant Enzymes ® (MS-AOE ® ), an rMnSOD obtained from a mutant high-temperature-resistant SOD strain, alleviates the mucositis caused by 5-fluorouracil, primarily in the first 3–5 days [ 172 ].…”
Section: Sod As a Detoxification Strategymentioning
confidence: 99%
“…Chemotherapy drugs can induce damage to the jejunum and colon, especially in the jejunum (18, 19). Therefore, we used the jejunum as the main tissue for the subsequent experiment.…”
Section: Resultsmentioning
confidence: 99%
“…To date, pathogenesis of 5-FU mediated intestinal mucositis is not completely elucidated. However, several underlying elements that are responsible for mucositis damages DNA and cellular and subcellular structures because of overproduction of ROS, uncontrolled in ammation that destroy intestinal homeostasis and natural microbial ora alterations (Yan et al 2020). In fact, ROS excessive production trigger the in ammatory pathways and pro-in ammatory cytokines production (Gelen et al 2018;Yan et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, several underlying elements that are responsible for mucositis damages DNA and cellular and subcellular structures because of overproduction of ROS, uncontrolled in ammation that destroy intestinal homeostasis and natural microbial ora alterations (Yan et al 2020). In fact, ROS excessive production trigger the in ammatory pathways and pro-in ammatory cytokines production (Gelen et al 2018;Yan et al 2020). Among many others, some basic transcription factors activated by ROS are NF-ĸB and MAPK proteins that increase the production of pro-in ammatory cytokines including TNF-α, IL-6 and IL-1β (Chang et al 2012;Song et al 2013;Zhang et al 2017).…”
Section: Discussionmentioning
confidence: 99%